The Investigation of the Effects of Ramadan Fasting on the Mood State of Family Physicians, Does Ramadan Fasting have a Protective Effect on Human Psychology? (Global Journal of Science Frontier Research, 2023)
Abstract not found
Keywords: depression; anxiety; stress; ramadan fasting; psychology